Effectiveness of Classroom Management Strategies in Reducing Off-Task Behavior - Abidin, Zainal; Qusairi, Ahmad (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2026)
Off-task behavior of students is a major challenge in the learning process at various levels of education, including at MA Riyadhul Ulum Pasuruan. This behavior can disrupt student concentration, reduce the effectiveness of the learning process, and potentially reduce academic results. Therefore, it is important to examine the classroom management strategies applied and their effectiveness in reducing this behavior. The purpose of this study was to analyze and evaluate the implementation of positive discipline strategies and behavioral reinforcement as an effort to control off-task behavior in class XII MA Riyadhul Ulum Pasuruan. The approach used was qualitative research with data collection methods through observation, semi-structured interviews, and documentation for one semester. Data analysis was carried out thematically to identify patterns and relationships between the strategies applied and the results obtained. The results showed that the implementation of positive discipline and behavioral reinforcement consistently increased student engagement and significantly reduced off-task behavior. Teachers who build good relationships and create a pleasant learning atmosphere show more effective results. However, environmental factors and classroom atmosphere still influence the success of the strategy. The suggestions from this study are the importance of ongoing training for teachers, adjusting strategies based on student characteristics, and improving supporting facilities so that the learning environment is more conducive. This research is expected to be a practical and theoretical reference to improve effective classroom management in the madrasah educational environment.